Miracles and Material Life: Rice, Ore, Traps and Guns in Islamic Malaya (by Teren Sevea): Cambridge University Press, 2020. 290 pages. (American Journal of Islam and Society, 2022)
Miracles and Material Life by Terenjit Sevea feels like the grand opening of an independent bookstore you just happened to pass by.  The vaults of an enthusiastic collector are finally opened, and every nook and cranny you investigate promises an exhilarating,  unexpected spark. The central focus of Sevea’s microhistory is the Islamic miracle worker (“pawang” or “bomoh”) in late-nineteenth  and early-twentieth century Malaya. Building on his creative engagement with Jawi manuscripts, and wide-ranging scholarship on  Sufism, Islamic material culture, and Islam in South and Southeast Asia, Sevea demonstrates how these extraordinary figures  manifested Islamic tradition and shaped colonial labor practices, and show how the Sufi networks, local forms of life, and labor contingencies in which these Islamic miracle workers were enmeshed animated their Islamic practice and impacted modern Malaya. This monograph will be especially valuable to scholars working on Islam and modernity, Sufism, and Islam in Southeast Asia. For those  fields, Sevea fleshes out critically overlooked facets of Islamic tradition. But Sevea’s analysis will also add to fields as wide-ranging as  history of science, material religion studies, gender studies, ethnic studies, ecocriticism, and postcolonial studies. Like the  forementioned bookstore, a short engagement with Miracles and Material Life will yield immediate finds, but the real gems will come  from a careful combing through during pensive afternoons or intense exploration with curious friends.